Morze i muzyka polifoniczna. Uwagi o wierszu "Sól konstrukcji" Mirona Białoszewskiego - Wiśniewski, Jerzy (Acta Universitatis Lodziensis. Folia Litteraria Polonica, 2009)
In the poem Sól konstrukcji from the cycle of poems Pokrewieństwa in the volume Obroty rzeczy 1956 (The Revolution o f Things), Miron Białoszewski describes a waving sea, which leads to discovering its hidden nature, surprisingly similar to the structural characteristics of polyphonic music - exemplified by the form of a motet and the works of Bach. Searching for affinities and similarities between distant things, Białoszewski discovers the harmony and internal cohesion of the world. It becomes possible when all stereotypic opinions and cliches are rejected and we perceive a new and unknown “revolution of things”.